Os efeitos da conversão de habitat nas comunidades de mamíferos: comparando a composição e a configuração da paisagem - Pedroso, Rayssa Cristina Faria (2019)
The conversion of native habitats into agriculture and pasture compromises landscape composition andconfiguration, causing ambivalent effects on biodiversity due tothe influence on different ecological dynamics for different species. However, these effects may not be understood if accessed at inappropriate spatial scales. Thus, identifying the "scale of effect" in which each landscape variable influences the different species responses is relevant to understand how the modified landscapes affect biodiversity. In this study, we evaluated how three variables of landscape composition (proportion of forest, coffee crop and pasture) and two of configuration (number of fragments and mean nearest neighbor distance) affect the species richness and composition of medium and large mammals, considering a multiscale approach. As coffee production and livestock farming are the main agricultural activities and the main causes of habitat loss and fragmentation in the region, we recorded medium and large mammal communities in 13 landscapes with predominantly coffee and pasture. First, we accessed the local and regional species richness. Then, we built distance-based linear models to identify the scales of effect of the landscape variables and verify the influence of landscape on mammalian richness and composition. We found that the local species richness is depaupered and the regional richness represents 67% of the probable species occurring in the region. The scales of effect varied among landscape variables probably due to the different variables affect different aspects of organisms' ecological requirements. Finally, we verified that the landscape composition was the most relevant to explain bothspecies richness and composition. The proportion of pasture in the landscape explained the variation of species richness in the smallest scale evaluated (250 m), while the proportion of forest explained the variation of the species composition in an intermediate scale (750 m). In addition, the proportion of pasture in the landscape had a positive influence on species richness, indicating that this matrix may favor the presence of generalist species and / or this result is due to the higher concentration of species in the fragments immersed in this matrix. These results suggest that considering different biodiversity responses is important to understand different aspects of landscape influence on biodiversity. In addition, the landscape composition is fundamental for species persistence and, therefore, both the forest cover and the matrices should be considered to improve strategies of species conservation. Finally, generalizing a spatial scale can lead to incomplete or erroneous interpretations of the influence of landscape on medium and large mammal communities.